A study on the sintering of ultrafine grained tungsten with Ti-based additives. (June 2017) - Ren, Chai; Koopman, Mark; Zak Fang, Z.; Zhang, Huan; van Devener, Brian
Abstract: Tungsten (W) is a brittle material at room temperature making it very difficult to fabricate. Although the lack of ductility remains a difficult challenge, nano-sized and ultrafine grain (UFG) microstructures offer potential for overcoming tungsten's room temperature brittleness. One way to manufacture UFG W is to compact and sinter nanosized W powder, however, it is a non-trivial task to control grain growth during sintering. In an effort to inhibit grain growth, the effect of Ti-based additives on the densification and grain growth of nano-W powders was investigated in this study. The addition of 1 wt.% Ti into tungsten led to more than a 63% decrease in average grain size of sintered samples at comparable density levels. It was also found that sintering in Ar yielded a finer grain size than sintering in H2 at similar densities. Compared to conventional high temperature sintering, a lower temperature sintering cycle for a longer hold time resulted in both near-full density and fine grain size. The roles of the Ti additive include not only the inhibition of grain growth, but also the potential absorption of oxygen from W particles. Highlights: Addition of minor amounts of Ti led to a dramatic decrease in grain size of sintered W Sintering for long hold times at low temperature resulted in near-full density and fine grain size. The Ti additive functioned as a grain growth inhibitor. Ti addition may absorb oxygen from adjacent W grains or grain boundaries.